Cu(i) catalysed annulation of isothiocyanates/isocyanates with 2-iodo-sulfonamides: synthesis of benzodithiazines, benzothiadiazinones, benzothiazinylidene-anilines and benzothiazolylidene-anilines. Issue 28 (4th July 2019) - Sandeep, K.; Siva Reddy, Alla; Kumara Swamy, K. C.
Abstract : Cu(i )-catalysed reaction of 2-iodobenzene sulfonamides with aryl isothiocyanates leads to benzodithiazines but the corresponding reaction with aryl isocyanates affords benzothiadiazinones . Abstract : An efficient Cu(i )-catalysed cyclisation reaction of 2-iodobenzene sulfonamides with aryl-isothiocyanates and isocyanates that affords functionalised benzodithiazines and benzothiadiazinones, respectively, has been developed. Thus, in the reaction with aryl isothiocyanates (Ar–NCS), the CS moiety participates in the cyclisation leading to a dithiazine . By contrast, in the case of aryl isocyanates (Ar–NCO), the NC part is involved in the cyclisation and a thiadiazinone is obtained. Analogous reactions of isothiocyanates with N -tosyl-2-iodo-anilines and 2-iodo-benzyl sulfonamides afford (benzothiazin-2-ylidene)anilines and (benzothiazol-2-ylidene)anilines, respectively. Probable mechanistic pathways are briefly discussed.